1985
DOI: 10.1515/zna-1985-0703
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Desorbed Large Molecules in a Supersonic Jet

Abstract: A new technique of desorption of non volatile thermally unstable molecules into a supersonic jet has been developped. With this method isolated large molecules are now available for mass spectrometry as well as for spectroscopic studies at temperatures of a few Kelvin, thus avoiding spectral congestion. It could be demonstrated that molecules like tryptophane and retinal could be desorbed with an IR laser pulse without decomposition and be ionized with a second UV laser to form bare molecule ions without fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Large biological molecules are thermally unstable. Thus, for observation in the gas phase, they have to be evaporated by special laser desorption techniques . Ionization of neutrals is performed by multiphoton ionization by UV laser pulses, a technique that has been proven to be a suitable tool for mass spectrometrical analysis. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large biological molecules are thermally unstable. Thus, for observation in the gas phase, they have to be evaporated by special laser desorption techniques . Ionization of neutrals is performed by multiphoton ionization by UV laser pulses, a technique that has been proven to be a suitable tool for mass spectrometrical analysis. , …”
Section: Methodsmentioning
confidence: 99%
“…Thus, for observation in the gas phase, they have to be evaporated by special laser desorption techniques. 35 Ionization of neutrals is performed by multiphoton ionization by UV laser pulses, a technique that has been proven to be a suitable tool for mass spectrometrical analysis. 30,31 The experimental setup used here is similar to that of our previous experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Large biologically relevant molecules are thermal unstable and thus for examinations in the gas phase have to be evaporated by special laser desorption techniques. 27 The two-step laser technique consisting of laser desorption of neutral, intact molecules into a supersonic beam expansion and of subsequent resonant multiphoton ionization and dissociation by UV-laser pulses has been proven to be a suitable tool for mass spectrometrical analysis of large nonvolatile neutral molecules,27•28 polypeptides,29 and nucleotides30 in the gas phase up to a mass 2000 Da without decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Amirav et al have shown that electron impact ionization spectra can be greatly simplified by internally cooling the molecules in a jet expansion prior to ionization. We combine this advantage of jet cooling with both laser desorption and photoionization. This approach has been reported before with multiphoton ionization, usually with emphasis on spectroscopy and applied to aromatic molecules. The limitation to aromatic compounds follows from the fact that commercially available lasers require molecular absorption at visible or near-UV wavelengths. Therefore many aliphatic compounds are excluded, reducing the practical usefulness of the method for analytical purposes.…”
mentioning
confidence: 99%